2021
DOI: 10.3390/ijerph18157756
|View full text |Cite
|
Sign up to set email alerts
|

The Present State of Lithium for the Prevention of Dementia Related to Alzheimer’s Dementia in Clinical and Epidemiological Studies: A Critical Review

Abstract: Despite the unavailability of essential anti-dementia drugs, lithium may inhibit glycogen synthase kinase-3 (GSK-3) and decrease beta-amyloid and hyper-phosphorylated tau. In this review, we hypothesized that trace to standard levels of lithium (i.e., corresponding to the therapeutic levels for bipolar disorder) may be effective for dementia prevention. Excluding three insufficient level studies, we obtained two and one excellent clinical studies on standard and trace lithium levels, respectively, all of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
3
13
0
4
Order By: Relevance
“…The present finding of lithium treatment-induced enhancement of whole-brain functional connectivity is consistent with previous studies reporting that lithium can improve the cognitive impairment in patients diagnosed with mild cognitive impairment or dementia (34,35). Implicated mechanisms for these lithium benefits include inhibition of glycogen synthase kinase-3 and reduction of beta-amyloid and hyper-phosphorylated tau (34,35). Our data, from a large-scale imaging perspective, provide evidence suggesting that lithium can improve cognitive impairments by enhancing functional connectivity on a whole-brain level.…”
Section: Discussionsupporting
confidence: 93%
“…The present finding of lithium treatment-induced enhancement of whole-brain functional connectivity is consistent with previous studies reporting that lithium can improve the cognitive impairment in patients diagnosed with mild cognitive impairment or dementia (34,35). Implicated mechanisms for these lithium benefits include inhibition of glycogen synthase kinase-3 and reduction of beta-amyloid and hyper-phosphorylated tau (34,35). Our data, from a large-scale imaging perspective, provide evidence suggesting that lithium can improve cognitive impairments by enhancing functional connectivity on a whole-brain level.…”
Section: Discussionsupporting
confidence: 93%
“…The dosages of chronic lithium treatment were based on previous studies ( Hopkins & Gelenberg, 2000 ; Ishii et al, 2021 ; Katz et al, 2022 ; Shvartsur et al, 2022 ) indicating safe and therapeutic lithium plasma levels (≥0.4 mEq/L). According to our previous study ( Gao et al, 2021 ), plasma analysis showed a lithium plasma level of 0.0484±0.0022 mEq/L in the control group and 0.5523±0.1615 mEq/L in the lithium-treated group, maintained within the patient therapeutic range, i.e., 0.4 mEq/L to 1.0 mEq/L ( Ishii et al, 2021 ). Therapeutic lithium levels in plasma can be maintained at ≥0.5 mEq/L for >2 h after a single administration lithium or chronic lithium treatment in rodents ( Morrison et al, 1971 ).…”
Section: Methodsmentioning
confidence: 99%
“…Соли лития способны усиливать аутофагию при многих нейродегенеративных заболеваниях путем удаления токсичных белковых агрегатов и улучшения состояния митохондрий, также способствуя нейрогенезу гиппокампа. Терапевтические концентрации лития значительно снижают уровни нерастворимого τ-белка и блокируют продукцию β-амилоидных пептидов про болезни Альцгеймера за счет ингибирования GSK-3β [46].…”
Section: Multidirectional Action Of Glycogen Synthase-3β Kinaseunclassified